1989
DOI: 10.1159/000116385
|View full text |Cite
|
Sign up to set email alerts
|

Mononeuritis multiplex with Brachial Plexus Neuropathy Coincident with <i>Mycoplasma pneumoniae </i>Infection

Abstract: Mycoplasma pneumoniae infection has been associated with a variety of neurologic complications involving the central nervous system, the peripheral nervous system and muscle. We present a patient who developed a previously unreported complication: mononeuritis multiplex. This consisted of a severe brachial plexus neuropathy with contralateral cervical monoradiculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Kidron et al had reported C6 root involvement with paraspinal denervation. 56 Whether a similar process can selectively involve the cervical plexus and the dorsal spinal nerves can only be confirmed by studying the histology of paraspinal muscles and dorsal spinal nerves early in the course of the illness.…”
Section: Described a 72mentioning
confidence: 99%
“…Kidron et al had reported C6 root involvement with paraspinal denervation. 56 Whether a similar process can selectively involve the cervical plexus and the dorsal spinal nerves can only be confirmed by studying the histology of paraspinal muscles and dorsal spinal nerves early in the course of the illness.…”
Section: Described a 72mentioning
confidence: 99%
“…In older people, neurogenic changes are often found on muscle biopsy, especially in the cervical and lumbar paraspinal muscles 1. Direct impingement of paraspinal nerves has not been reported in patients with camptocormia, but Kidron et al 3 reported spinal root involvement with paraspinal muscle denervation in a patient with mononeuritis multiplex. Our patient also showed denervation and neuropathic discharges in paraspinal muscle on EMG.…”
Section: Discussionmentioning
confidence: 99%
“…Las manifestaciones extrapulmonares a nivel neurológico se han descrito: encefalitis [ 146 , 147 ], encefalomielitis diseminada [ 148 ], infarto cerebral [ 149 , 150 ], cerebelitis aguda [ 151 ], mielitis transversa y síndrome de Guillain-Barré [ 152 , 153 ], enfermedad de Weston Hurt [ 154 ], necrosis estriatal bilateral reversible [ 155 ]; meningitis crónica, hipertensión intracraneal y plexopatía braquial [ 156 , 157 ]; neurorretinits bilateral [ 158 ]; y casos de psicosis en adultos [ 159 ]. A nivel dermatológico: urticaria [ 160 ], dermatosis pustulosa subcorneal [ 161 ], púrpura de Henoch-Schönlein [ 162 ], úlcera vulvar [ 163 ], eritema multiforme [ 164 ] y exantema mucocutáneo inducido por M. pneumoniae [ 165 , 166 ].…”
Section: Especies Implicadas En Patología Humanaunclassified